Association of polymorphisms in exon 6 and 3′-untranslated region of the OLR1 gene with milk production traits in Sahiwal cattle. Issue 1 (31st December 2023) - Mir, Mohsin Ayoub; Ahmad, Tavsief; Gupta, Ishwar Dayal; Magotra, Ankit; Singh, Arun Pratap; Singh, Manvendra; Pandit, Arif; Muzhupilezhikethu Raveendran, Vineeth
ABSTRACT: The present investigation was undertaken to explain the association of SNPs (single nucleotide polymorphisms) in exon 6 and 3′-UTR of OLR 1 gene with milk traits in Sahiwal cattle. Milk traits were observed from 328 Sahiwal cows sired by 64 bulls viz: – First lactation 305 days milk yield (Kg) (FL305MY), Average test day milk yield (Kg) (ATDMY), Average test day fat percentage (%) (ATDFP) and Lactational fat yield (Kg) (LFY). The animal model was used to estimate the breeding values for FL305MY and LFY. The traits ATDMY and ATDFP were corrected for significant non-genetic factors by using LSML-Harvey and subsequently used for association studies. A total of 130 animals for PCR-RFLP and 103 for sequencing were screened through three sets of primers for the presence of polymorphisms in exon 6 and 3′-UTR of the OLR1 gene. The CC genotype of SNP C337A in the 3′-UTR of OLR1 gene had a significant effect ( p < 0.01) on ATDFP and LFY. Allele combination CGC had a positive effect ( p < 0.05) on ATDFP. Identified SNP C337A and CCGGCC haplotype can be used as potential markers for improving milk yield and composition traits in Sahiwal cattle.